Potential Targets' Analysis Reveals Dual PI3K/mTOR Pathway Inhibition as a Promising Therapeutic Strategy for Uterine Leiomyosarcomas-an ENITEC Group Initiative - Cuppens, Tine; Annibali, Daniela; Coosemans, An; Trovik, Jone; Ter Haar, Natalja; Colas, Eva; Garcia-Jimenez, Angel; Van de Vijver, Koen; Kruitwagen, Roy P M; Brinkhuis, Mariël; Zikan, Michal; Dundr, Pavel; et al. (Clinical cancer research, 2017)
Purpose: Uterine sarcomas are rare and heterogeneous tumors characterized by an aggressive clinical behavior. Their high rates of recurrence and mortality point to the urgent need for novel targeted therapies and alternative treatment strategies. However, no molecular prognostic or predictive biomarkers are available so far to guide choice and modality of treatment.Experimental Design:We investigated the expression of several druggable targets (phospho-S6S240ribosomal protein, PTEN, PDGFR-α, ERBB2, and EGFR) in a large cohort of human uterine sarcoma samples (288), including leiomyosarcomas, low-grade and high-grade endometrial stromal sarcomas, undifferentiated uterine sarcomas, and adenosarcomas, together with 15 smooth muscle tumors of uncertain malignant potential (STUMP), 52 benign uterine stromal tumors, and 41 normal uterine tissues. The potential therapeutic value of the most promising target, p-S6S240, was tested in patient-derived xenograft (PDX) leiomyosarcoma models.Results:In uterine sarcomas and STUMPs, S6S240phosphorylation (reflecting mTOR pathway activation) was associated with higher grade (P= 0.001) and recurrence (P= 0.019), as shown by logistic regression. In addition, p-S6S240correlated with shorter progression-free survival (P= 0.034). Treatment with a dual PI3K/mTOR inhibitor significantly reduced tumor growth in 4 of 5 leiomyosarcoma PDX models (with tumor shrinkage in 2 models). Remarkably, the 4 responding models showed basal p-S6S240expression, whereas the nonresponding model was scored as negative, suggesting a role for p-S6S240in response prediction to PI3K/mTOR inhibition.Conclusions:Dual PI3K/mTOR inhibition represents an effective therapeutic strategy in uterine leiomyosarcoma, and p-S6S240expression is a potential predictive biomarker for response to treatment.Clin Cancer Res; 23(5); 1274-85. ©2017 AACR.
Keywords: Phosphatidylinositol 3-Kinases; xenogenní modely - testy protinádorové aktivity; Molecular Targeted Therapy; nádory dělohy; nádorové biomarkery; ribozomální protein S6; Signal Transduction; lidé; ženské pohlaví; myši; Leiomyosarcoma; Xenograft Model Antitumor Assays; TOR Serine-Threonine Kinases; Biomarkers, Tumor; fosfatidylinositol-3-kinasy; Humans; Mice; TOR serin-threoninkinasy; regulace genové exprese u nádorů; Animals; inhibitory fosfoinositid-3-kinasy; Uterine Neoplasms; zvířata; leiomyosarkom; cílená molekulární terapie; Gene Expression Regulation, Neoplastic; fosforylace; přežití bez známek nemoci; Phosphorylation; Ribosomal Protein S6; Female; Disease-Free Survival; signální transdukce; Phosphoinositide-3 Kinase Inhibitors; prognóza; Prognosis